2006
DOI: 10.1517/13543784.15.8.873
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional neuroprotective drugs targeting monoamine oxidase inhibition, iron chelation, adenosine receptors, and cholinergic and glutamatergic action for neurodegenerative diseases

Abstract: A new paradigm is emerging in the targeting of multiple disease aetiologies that collectively lead to neurodegenerative disorders such as Parkinson's disease, Alzheimer's disease, post-stroke neurodegeneration and others. This paradigm challenges the widely held assumption that 'silver bullet' agents are superior to 'dirty drugs' when it comes to drug therapy. Accumulating evidence in the literature suggests that many neurodegenerative diseases have multiple mechanisms in their aetiologies, thus suggesting tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 103 publications
0
36
0
Order By: Relevance
“…These authors combined the antioxidant chelator moiety of an 8-hydroxyquinoline derivative of the neuroprotective brain-permeable iron chelator VK-28 [42] with the propargylamine moiety found in compounds such as rasagiline and deprenyl. The resulting compound, HLA20, was identified as a potential lead compound for further studies and has been characterized as a brain-permeable iron chelator and a brain-selective MAO inhibitor that possesses the propargyl neuroprotective moiety [43].…”
Section: Metal Chelators/mao-b Inhibitors With Additional Cotargeted mentioning
confidence: 99%
“…These authors combined the antioxidant chelator moiety of an 8-hydroxyquinoline derivative of the neuroprotective brain-permeable iron chelator VK-28 [42] with the propargylamine moiety found in compounds such as rasagiline and deprenyl. The resulting compound, HLA20, was identified as a potential lead compound for further studies and has been characterized as a brain-permeable iron chelator and a brain-selective MAO inhibitor that possesses the propargyl neuroprotective moiety [43].…”
Section: Metal Chelators/mao-b Inhibitors With Additional Cotargeted mentioning
confidence: 99%
“…Ladostigil also has been reported to enhance soluble amyloid precursor protein (APP)-␣ secretion via the protein kinase C-MAP kinasedependent pathway, and to decrease the levels of holo-APP (i.e., actions that favor cell viability). [13][14][15] Thus, ladostigil represents a new drug class that is potentially suitable for the treatment of Alzheimer's disease (AD). Patients with AD require therapies that will delay the progression of the disease, and they may suffer from impaired attention, impaired memory, extrapyramidal disorders, and depression.…”
Section: Rational Molecular Designmentioning
confidence: 99%
“…131,132 A growing number of compounds have been specifically designed by conjugating two or more distinct pharmacophores, exhibiting safe dosage use and interaction with multiple molecular pathways targets, which are different from the unconjugated pharmacophore. 32,124 The multifunctional "dirty" drug, ladostigil, was designed to possess the neuroprotective activity established for rasagiline, and address the therapeutic requirements needed to delay the progression of neurodegenerative diseases (PD with dementia, Lewy Body disease, and dementia Lewy Body disease with extrapyramidal symptoms) with features of dementia, behavioral abnormalities, depression, and extrapyramidal symptoms. Thal and co-workers 133 introduced the notion that these alterations are restricted to specific regions of the brain and may be associated with several phases of premorbidity (or preclinical debut stages) of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…32,124 A recent study 125 has demonstrated that M-30 has a wide range of pharmacological activities, including a significant downregulation of membrane-associated holo-APP levels in the mouse hippocampus and in SH-SY5Y neuroblastoma cells, presumably by chelating intracellular iron pools. Indeed, M-30 was found to suppress translation of a luciferase reporter mRNA via the APP 5'UTR sequence that includes the APP IRE.…”
Section: App Regulation and A␤ Peptide Reductionmentioning
confidence: 99%